2010
DOI: 10.1002/rcm.4682
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of an evolved gas analysis ion attachment mass spectrometer

Abstract: We designed a simple evolved gas analysis (EGA) system to act as a sampler between solid samples at atmospheric pressure and the high vacuum inside a mass spectrometer. The newly designed stainless steel system is simple, small and rugged and fulfills all the basic requirements for EGA. The temperature is programmable with 60 degrees C/min as the maximum heating rate and the temperature range is up to 600 degrees C. With this system coupled with lithium ion attachment mass spectrometry (IAMS), it is possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A microceramic heater is fastened to the holder with the sampler at the upper end and a thermocouple at the bottom. A DIP temperature controller allows the target temperature, heating rate, and length of constant‐temperature periods in each step to be adjusted …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A microceramic heater is fastened to the holder with the sampler at the upper end and a thermocouple at the bottom. A DIP temperature controller allows the target temperature, heating rate, and length of constant‐temperature periods in each step to be adjusted …”
Section: Methodsmentioning
confidence: 99%
“…A DIP temperature controller allows the target temperature, heating rate, and length of constant-temperature periods in each step to be adjusted. [24] EGA-IAMS analysis was carried out with 0.1 mg of the sample, which was heated from 25 to 300 C at a rate of 128 C min -1 . The molecular species (neutral molecules or radicals) attached to the Li + and produced corresponding [M + Li] + adducts.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…The details of the construction of the IIF inlet system have already been reported. 29 The IIF was programmed so that the temperature increased constantly at 20 C min À1 from 50 to 600 C and then held steady at 600 C for 20 min. Decomposition products were swept from the furnace through an orifice into the mass spectrometer by a N 2 gas stream, typically at a flow rate of 250-300 mL min À1 and a pressure of 1 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…In previous work, we developed, extensively tested, and optimized a novel technique based on soft ionization Li + ion attachment mass spectrometry (IAMS). [25][26][27][28][29][30] One of the great advantages of this efficient, sensitive technique is that it can be used to directly analyze gaseous compounds, because the mass spectra contain only peaks for quasi-molecular ions formed by Li + attachment to chemical species, including free radicals. We expected 25,28,29 that the coupling of EGA and IAMS would work well for analysis of nonvolatile, untreated, complex samples such as lacquers, because the simplicity of ion attachment spectra permits the analysis of mixtures whose electron impact spectra would be difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we also observed this same tendency with respect to the nature of the products. Because a quantitative assessment and rigorous analysis of these closed-shell molecular species are beyond the scope of this paper, we have reported the details elsewhere [18].…”
Section: Classification Analysismentioning
confidence: 99%